Respuesta :

Answer:

K

K -> H

H

B -> ~H

H not B (sorry I couldn't type out the symbol)

~B

Step-by-step explanation:

Verbally, what's happening is this:

We have an assertion of K. Since K -> H (K implicates H), and B -> ~H (B implicates a negation of H), a negation of B (~B) is proven. (In this entire process, nothing is given about the symbols except K is true, hence the assertion, which then implicates that H is true and that B is negated since B implicates that negated H is true when in fact it is the opposite.)

Formally, the answer would be the following:

K

K -> H

H

B -> ~H

H not B (sorry I couldn't type out the symbol)

~B

Hope this helped!